PEMBELAJARAN MATEMATIKA MENGGUNAKAN CD INTERAKTIF AMT BERBASIS LECTORA INSPIRE UNTUK SISWA SD - Sukamto, Sukamto; Wardani, Asry Kusuma (Mimbar Sekolah Dasar, 2016)
The purpose of this research considers the effectiveness of mathematic learning using lectora inspire based interactive CD in primary school. This research is a research and development with design of ADDIE. The validity of he returns products developed by votes validate media experts and material to obtain a valid criterion.  Products in the validation by experts and the media matter experts, and then tested. Sample test grade four  students of elementary school Tandang 01 Semarang.  Results of the media validation analysis experts the average percentage of media ideals, respectively for 68.00% and 89.58%. Results of the validation  analysis matter experts the average percentage of media ideals, respectively for 74.67% and 90.42%, and the response to all students in grade IV B of elementary school of Tandang  01 Semarang  by 87.64%. Based on the test results are known t0 t over table (9.056 2.030). Differences in student learning outcomes before and after being treated was 59%, from the analysis, AMT interactive CD categorized as very well, so it can be applied in teaching.Keywords: interactive CD, lectora inspire, learning outcomes.